2009
DOI: 10.1073/pnas.0907658106
|View full text |Cite
|
Sign up to set email alerts
|

A backward progression of attentional effects in the ventral stream

Abstract: The visual processing of behaviorally relevant stimuli is enhanced through top-down attentional feedback. One possibility is that feedback targets early visual areas first and the attentional enhancement builds up at progressively later stages of the visual hierarchy. An alternative possibility is that the feedback targets the higher-order areas first and the attentional effects are communicated "backward" to early visual areas. Here, we compared the magnitude and latency of attentional enhancement of firing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
188
6
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 272 publications
(237 citation statements)
references
References 43 publications
42
188
6
1
Order By: Relevance
“…We found a "backward" progression of attentional effects on synchrony in the ventral stream, with the strongest enhancement of synchrony in V4 and the weakest effects in V1, suggesting that V4 might be responsible for the attentional effects in upstream areas through feedback projections (22). Another recent study found an enhancement of gamma synchrony with attention in V4 but a suppression of gamma synchrony in V1 (49).…”
Section: Discussionsupporting
confidence: 42%
See 1 more Smart Citation
“…We found a "backward" progression of attentional effects on synchrony in the ventral stream, with the strongest enhancement of synchrony in V4 and the weakest effects in V1, suggesting that V4 might be responsible for the attentional effects in upstream areas through feedback projections (22). Another recent study found an enhancement of gamma synchrony with attention in V4 but a suppression of gamma synchrony in V1 (49).…”
Section: Discussionsupporting
confidence: 42%
“…Total cells recorded in the superficial layers of V1, V2, and V4 were 67, 13, and 73, respectively, and the corresponding totals in the deep layers were 14, 47, and 12. The superficial V4 cells included 47 cells reported in previous studies of coherence and attention in V4 (1), and individual cells from recordings in all three areas were included in a previous study of attentional effects on firing rate latencies (22). Cells were recorded in two monkeys performing a task of directed spatial attention (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Attentional signals are particularly prominent in V4, influencing 73% of recorded neurons according to the recent study by Buffalo et al (2010). FEF afferents are unusual in forming synapses in all layers of V4.…”
Section: Significance Of Laminar Specificitymentioning
confidence: 90%
“…The most direct and likely route is the monosynaptic connection from the FEF to the posterior parietal and the occipital lobe (Huerta et al, 1987;Stanton et al, 1995), including area V1 (Clavagnier et al, 2004), V2 (Markov et al, 2011), and V4 (Stanton et al, 1995;Barone et al, 2000). In the occipital lobe, the earliest and strongest effects of the attentional signal are seen in V4, with progressively later and lesser effects in V2 and V1 (Buffalo et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the ventral stream, neurons in visual area 4 (V4) filter irrelevant information from the RF (Moran and Desimone, 1985;Luck et al, 1997). It has also been shown that attentional effects are larger and earlier in V4 than V1 and visual area 2 (V2) (Mehta et al, 2000;Buffalo et al, 2010) and lesions in V4 affect the filtering of distracters at high resolution in downstream area TE (Buffalo et al, 2005). These findings suggest that V4 plays important roles in providing top-down signals to visual areas in the ventral stream.…”
Section: Introductionmentioning
confidence: 99%